INFLUENCE ANALYSIS EXPENSE OF PROMOTION, GENERAL EXPENSE AND VOLUME OF TRADING TO PROFIT AT SAMIDI GLASS & CRAFT GONDANG, BALANCE, SUKOHARJO - Jumingan, Jumingan; Sarwanti, Sarwanti (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2012)
AbstractPromotion is processing satisfaction giving to consumer to get profit. Sensible promotion become determinant success of every small or big company, orientation which profit or nirlaba, domestic and or global. Company management must can plan correctly and can estimate in in all change influence of expense of promotion, general expense, volume of trading and selling price to profit. This research internal issue formula is : 1) Are there influence expense of promotion to profit at Samidi Glass & Craft Gondang, Balance, Sukoharjo ?. 2) Are there general expense influence to profit at Samidi Glass & Craft Sukoharjo ?. 3) Are there volume of trading influence to profit at Samidi Glass & Craft Sukoharjo. Purpose of in this research is: 1) To know influence expense of promotion to profit at Samidi Glass & Craft Sukoharjo. 2) To know general expense influence to profit at Samidi Glass & Craft Sukoharjo. 3) To know volume of trading influence to profit at Samidi Glass & Craft Gondang, Balance, Sukoharjo. Hypothesis submitted is: 1) Anticipated there are influence expense of promotion to profit. 2) Anticipated there are general expense influence to profit. 3) Anticipated there are volume of trading influence to profit.Analyzer applied in this research is Uji Data: Data Normality Test and Uji Linieritas, Hypothesis Test: Parsial Regression Analysis, Regression Analysis Linieritas Berganda, Test Signifikasi: Test t, Test F, Uji R2 ( Coefficient of determination).Based on result of analysed hence inferential : 1) There is influence expense of promotion to profit. 2) there is general expense influence to profit. 3) there is volume of trading influence to profit. Keyword : Expense Of Promotion, General expense, Volume of trading and Profit.